Hubungan Genre Musik dengan Gaya Berpakaian Mahasiswa - Marchelino, Gabriel; Junaidi, Ahmad (Kiwari, 2026)
Music is not merely a companion to fill the silence, and clothing is not merely protection for the body. Both have merged into a silent language that tells the story of who they really are. This study stems from an interesting phenomenon on campus, where the diversity of music genres—from energetic hip-hop beats, stylish K-pop aesthetics, to poetic indie melodies—seems to be in harmony with the clothing styles of their listeners. This study aims to trace the relationship: to what extent does the music listened to influence students' decisions in choosing their clothing style? This study views students as active individuals who consciously choose music to fulfil their inner needs. This satisfaction is then expressed through artifactual communication, making clothing a ‘stage’ for self-presentation. Using a quantitative approach, this study voices the opinions of 100 Tarumanagara University students who participated as respondents. The collected data was then statistically processed to identify patterns of cause and effect. The results of this study tell a powerful story: there is a clear and significant influence between the genre of music listened to and students' clothing styles. The findings show that 50.1% of the variation in students' clothing styles is shaped by their musical tastes. This confirms that for Tarumanagara University students, music is an integral part of their identity. What enters their ears is visualised through what they wear, making music one of the main determinants in expressing their identity in social spaces. Musik bukan sekadar teman pengisi kesunyian, dan pakaian bukan hanya sekadar pelindung tubuh. Keduanya telah melebur menjadi bahasa diam yang menceritakan siapa mereka sebenarnya. Penelitian ini berangkat dari fenomena menarik di lingkungan kampus, di mana keragaman genre musik—mulai dari beats Hip-Hop yang energik, estetika K-Pop yang stylish, hingga alunan Indie yang puitis tampak selaras dengan gaya berpakaian yang dikenakan oleh para pendengarnya. Penelitian ini bertujuan untuk menelusuri jejak hubungan tersebut: seberapa besar musik yang didengar mampu memengaruhi keputusan mahasiswa dalam memilih gaya berpakaian mereka? Penelitian ini memandang mahasiswa sebagai individu aktif yang sadar memilih musik untuk memenuhi kebutuhan batinnya. Kepuasan inilah yang kemudian terpancar keluar melalui komunikasi artifaktual, menjadikan pakaian sebagai "panggung" presentasi diri. Melalui pendekatan kuantitatif, penelitian ini menyuarakan pendapat dari 100 mahasiswa Universitas Tarumanagara yang menjadi responden. Data yang terkumpul kemudian diolah secara statistik untuk melihat pola hubungan sebab-akibat yang terjadi. Hasil penelitian ini membawa sebuah cerita yang kuat: terdapat pengaruh yang nyata dan signifikan antara genre musik yang didengar terhadap gaya berpakaian mahasiswa. Temuan data menunjukkan bahwa sebesar 50,1% variasi gaya berpakaian mahasiswa dibentuk oleh selera musik mereka. Hal ini menegaskan bahwa bagi mahasiswa Universitas Tarumanagara, musik adalah bagian tak terpisahkan dari identitas diri. Apa yang masuk ke telinga mereka, tervisualisasi melalui apa yang mereka kenakan, menjadikan musik sebagai salah satu penentu utama dalam mengekspresikan jati diri di ruang sosial.